2020
DOI: 10.1002/eat.23400
|View full text |Cite
|
Sign up to set email alerts
|

Orthorexia nervosa is associated with positive body image and life satisfaction in Chinese elderly: Evidence for a positive psychology perspective

Abstract: Objective Obsessive attention to healthy eating might paradoxically lead to physical and psychosocial impairments, a potential eating disorder termed orthorexia nervosa (ON). An ongoing debate concerns whether ON should be categorized as an eating disorder, an obsessive–compulsive disorder, or a mental disorder at all. A missing voice in this debate is ON in the elderly, which remains unknown, despite health being a more central issue in everyday life during old age. Similarly missing is ON in East Asia, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 51 publications
2
36
0
3
Order By: Relevance
“…In contrast to other self-report questionnaires measuring dietary behavior, which do not correlate negatively with BMI [ 36 ], the GDBI has methodological strengths and has advantages over other dietary behavior questionnaires. The association of dietary behavior and life satisfaction has already been identified in several studies supporting our findings [ 69 , 70 , 71 ]. However, the GDBI did not capture actual food intake in contrast to typical food frequency questionnaires [ 12 , 13 ].…”
Section: Discussionsupporting
confidence: 92%
“…In contrast to other self-report questionnaires measuring dietary behavior, which do not correlate negatively with BMI [ 36 ], the GDBI has methodological strengths and has advantages over other dietary behavior questionnaires. The association of dietary behavior and life satisfaction has already been identified in several studies supporting our findings [ 69 , 70 , 71 ]. However, the GDBI did not capture actual food intake in contrast to typical food frequency questionnaires [ 12 , 13 ].…”
Section: Discussionsupporting
confidence: 92%
“…Lastly, the two final papers of the special issue focus on an understudied presentation of disordered eating characterized by an unhealthy obsession with healthy eating: orthorexia nervosa. Specifically, He, Zhao, Zhang, and Lin (2021) described the characteristics of orthorexia nervosa among older adults in China and suggested that orthorexia symptoms in this population may actually be associated with positive health outcomes, providing initial evidence for a positive psychological perspective of orthorexia, at least in China. In response, Hay (2021) provided an interesting commentary on whether or not orthorexia nervosa is an ED.…”
Section: Orthorexiamentioning
confidence: 99%
“…Although features of eating disorders such as drive for thinness, body dissatisfaction, and sex differences are not part of ON conceptually, the independence of orthorexic symptomatology from these features could not be demonstrated empirically. To put our results into perspective, however, we also need to mention that DOS scores were unrelated to features of disordered eating in two studies from China (15,26), indicating that there might be cultural differences in orthorexic symptomatology or in its measurement. Cultural differencesbetween China and Western countries in particular-have been previously noted in self-report measures of eating behavior and their correlates with the reasons for these differences remaining elusive (27,28).…”
Section: Discussionmentioning
confidence: 97%